Effect of salt deposition patterns on stress corrosion cracking - Elsherkisi, Mustafa; Duarte Martinez, Fabian; Mason-Flucke, Julian C.; Gray, Simon; Castelluccio, Gustavo M. (Springer, 2025)
While substantial research has been devoted to understanding environmental degradation mechanisms in Ni-base superalloys, the influence of solid contamination morphology on cracking remains comparatively underexplored. This study combines computational modeling and experimental approaches to investigate cracking behavior in CMSX-4 single-crystal superalloys exposed to salt deposition patterns in sulfur-rich environments at moderate temperatures. Utilizing phase-field computational models, we develop a digital twin of the experimental setup to examine crack propagation under varying deposition configurations. The findings reveal that salt deposition patterns can inhibit crack shielding, leading to increased crack lengths and shorter fatigue lives. A novel experimental salt configuration resulted in crack lengths extending from 300 μm to over 2 mm under static loading conditions and decreased corrosion-fatigue life by as much as 83%. The results demonstrate that modeling is a valuable tool to mitigate experimental uncertainty.
Keywords: 40 Engineering; 4016 Materials engineering